Calcium signaling affects migration and proliferation differently in individual cancer cells due to nifedipine treatment - Chovancova, Barbora; Liskova, Veronika; Miklikova, Svetlana; Hudecova, Sona; Babula, Petr; Penesova, Adela; Sevcikova, Angelika; Durinikova, Erika; Novakova, Marie; Matuskova, Miroslava; Krizanova, Olga (Biochemical pharmacology, 2020)
Several papers have reported that calcium channel blocking drugs were associated with increased breast cancer risk and worsened prognosis. One of the most common signs of breast tumors is the presence of small deposits of calcium, known as microcalcifications. Therefore, we studied the effect of dihydropyridine nifedipine on selected calcium transport systems in MDA-MB-231 cells, originating from triple negative breast tumor and JIMT1 cells that represent a model of HER2-positive breast cancer, which possesses amplification of HER2 receptor, but cells do not response to HER2 inhibition treatment with trastuzumab. Also, we compared the effect of nifedipine on colorectal DLD1 and ovarian A2780 cancer cells. Both, inositol 1,4,5-trisphosphate receptor type 1 (IP3R1) and type 1 sodium calcium exchanger (NCX1) were upregulated due to nifedipine in DLD1 and A2780 cells, but not in breast cancer MDA-MB-231 and JIMT1 cells. On contrary to MDA-MB-231 and JIMT1 cells, in DLD1 and A2780 cells nifedipine induced apoptosis in a concentration-dependent manner. After NCX1 silencing and subsequent treatment with nifedipine, proliferation was decreased in MDA-MB-231, increased in DLD1 cells, and not changed in JIMT1 cells. Silencing of IP3R1 revealed increase in proliferation in DLD1 and JIMT1 cells, but caused decrease in proliferation in MDA-MB-231 cell line after nifedipine treatment. Interestingly, after nifedipine treatment migration was not significantly affected in any of tested cell lines after NCX1 silencing. Due to IP3R1 silencing, significant decrease in migration occurred in MDA-MB-231 cells after nifedipine treatment, but not in other tested cells. These results support different function of the NCX1 and IP3R1 in the invasiveness of various cancer cells due to nifedipine treatment.
Keywords: vápníková signalizace; regulace genové exprese u nádorů; nádory vaječníků; nádory prsu; apoptóza; proliferace buněk; kolorektální nádory; trastuzumab; Female; Cell Line, Tumor; ženské pohlaví; Apoptosis; Gene Expression Regulation, Neoplastic; Colorectal Neoplasms; Nifedipine; lidé; blokátory kalciových kanálů; nifedipin; triple-negativní karcinom prsu; Sodium-Calcium Exchanger; Breast Neoplasms; inositol-1,4,5-trisfosfát - receptory; Ovarian Neoplasms; Triple Negative Breast Neoplasms; pohyb buněk; Receptor, ErbB-2; protinádorové látky imunologicky aktivní; receptor erbB-2; Calcium Channel Blockers; Calcium Signaling; Cell Proliferation; RNA Interference; pumpa pro výměnu sodíku a vápníku; Cell Movement; Trastuzumab; RNA interference; Inositol 1,4,5-Trisphosphate Receptors; Antineoplastic Agents, Immunological; nádorové buněčné linie; Humans